Communicating the risks of genetically modified organisms lessons learnt from an Irish field of cisgenic potatoes - Mullins, Ewen (Journal of experimental botany, 2019)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology.